Karakteristik Edible Film Aloe vera dengan Emulsi Extra Virgin Olive Oil dan Kitosan - Yoga Pratama; Miranda Miranda; Antonius Hintono (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
Edible film is a potential biodegradable packaging in the food industry. This research is aimed to determine the physical, chemical and mechanical properties of Aloe vera with extra virgin olive oil and chitosan emulsion edible film. Complete Randomized Design was used with five treatments and four repetitions. The treatments were composition ratio between Aloe vera gel and extra virgin olive oil (EVOO) - chitosan emulsion that consists of T1 (40:60), T2 (45:55), T3 (50:50), T4 (55:45) and T5 (60:40). The method used in this study included making Aloe vera gel and an emulsion of EVOO 1% (v/v) in chitosan 1% (b/v), homogenizing the materials, casting and drying. The results showed that range of film thickness, solubility, water vapor permeability, antioxidant activity, extension and tensile strength were 0.067-0.073 mm, solubility 48.70-65.73%, 1.39 × 10-5 – 1.77 × 10-5 g mmHg-1 m-1 h-1, 3.31-6.56%, 6.78-14.72% and 0.29-0.68 MPa. The edible film composition showed significant difference (p ≤ 0,05) for thickness, solubility, antioxidant activity, extension and tensile strength film, however, the water vapor permeability was not significantly different (p ≥ 0,05).